Biofuels Production from Catalytic Cracking of Palm Oil Using Modified HY Zeolite Catalysts over A Continuous Fixed Bed Catalytic Reactor - Istadi, I.; Riyanto, Teguh; Buchori, Luqman; Anggoro, Didi D.; Pakpahan, Andre W. S.; Pakpahan, Agnes J. (International Journal of Renewable Energy Development, 2021)
The increase in energy demand led to the challenging of alternative fuel development. Biofuels from palm oil through catalytic cracking appear as a promising alternative fuel. In this study, biofuel was produced from palm oil through catalytic cracking using the modified HY zeolite catalysts. The Ni and Co metals were impregnated on the HY catalyst through the wet-impregnation method. The catalysts were characterized using X-ray fluorescence, X-ray diffraction, Brunauer–Emmett–Teller (BET), Pyridine-probed Fourier-transform infrared (FTIR) spectroscopy, and Scanning Electron Microscopy (SEM) methods. The biofuels product obtained was analyzed using a gas chromatography-mass spectrometry (GC-MS) method to determine its composition. The metal impregnation on the HY catalyst could modify the acid site composition (Lewis and Brønsted acid sites), which had significant roles in the palm oil cracking to biofuels. Ni impregnation on HY zeolite led to the high cracking activity, while the Co impregnation led to the high deoxygenation activity. Interestingly, the co-impregnation of Ni and Co on HY catalyst could increase the catalyst activity in cracking and deoxygenation reactions. The yield of biofuels could be increased from 37.32% to 40.00% by using the modified HY catalyst. Furthermore, the selectivity of gasoline could be achieved up to 11.79%. The Ni and Co metals impregnation on HY zeolite has a promising result on both the cracking and deoxygenation process of palm oil to biofuels due to the role of each metal. This finding is valuable for further catalyst development, especially on bifunctional catalyst development for palm oil conversion to biofuels.